Insufficient evidence of benefit regarding mortality due to albumin substitution in HCC‐free cirrhotic patients undergoing large volume paracentesis. Issue 2 (February 2017) - Kütting, Fabian; Schubert, Jens; Franklin, Jeremy; Bowe, Andrea; Hoffmann, Vera; Demir, Muenevver; Pelc, Agnes; Nierhoff, Dirk; Töx, Ulrich; Steffen, Hans‐Michael
Abstract: Background: Current guidelines for clinical practice recommend the infusion of human albumin after large volume paracentesis. After inspecting the current evidence behind this recommendation, we decided to conduct a systematic review and meta‐analysis in order to address the effect of albumin on mortality and morbidity in the context of large volume paracentesis. Methods: We performed a comprehensive search of large databases and abstract books of conference proceedings up to March 15th 2016 for randomized controlled trials, testing the infusion of human albumin against alternatives ( vs no treatment, vs plasma expanders; vs vasoconstrictors) in HCC‐free patients suffering from cirrhosis. We analyzed these trials with regard to mortality, changes in plasma renin activity (PRA), hyponatremia, renal impairment, recurrence of ascites with consequential re‐admission into hospital and additional complications. We employed trial sequential analysis in order to calculate the number of patients required in controlled trials to be able to determine a statistically significant advantage of the administration of one agent over another with regard to mortality. Results: We were able to include 21 trials totaling 1277 patients. While the administration of albumin prevents a rise in PRA as well as hyponatremia, no improvement in strong clinical endpoints such as mortality could be demonstrated. Trial sequential analysis showed that at least 1550 additional patients need to be recruited into RCTs and analyzed with regard to this question in order to detect or disprove a 25% mortality effect. Conclusions: There is insufficient evidence that the infusion of albumin after LVP significantly lowers mortality in HCC‐free patients with advanced liver disease.